Effects of tumour stage, comorbidity and therapy on survival of laryngeal cancer patients: a systematic review and a meta-analysis - Rudolph, Elisabeth; Dyckhoff, Gerhard; Becher, Heiko; Dietz, Andreas; Ramroth, Heribert (European archives of oto-rhino-laryngology and head & neck, 2011)
Laryngeal cancer is the second most common cancer of the respiratory tract with a relative 5-year survival over all tumour sites in the USA (61.6%; SEER 2009), which is much better than other head and neck cancers. The aim of this paper is to review and summarise data on the survival of laryngeal cancer patients. Literature search was conducted to identify articles in PubMed up to June 2009. Thirty studies with different study aims including sufficient information on survival of laryngeal cancer patients were identified. The 5-year overall survival ranged from 0 to 100%, depending on the T- and N-category, therapeutic approach and tumour location. The involvement of other factors such as genetics, nutrition and lifestyle habits remains uncertain. Our meta-analysis on a subgroup of published studies yielded an overall 5-year relative survival rate of 64.2% (95% confidence interval 63.7-64.7%). Different study aims and patient selection criteria prohibit general conclusions. However, this review may provide an actual picture of the complexity of factors influencing the survival of laryngeal cancer patients.
Published online: 19 October 2010
Gesehen am 21.09.2022